Global classroom : multicultural approaches and organizational strategies in teaching and learning business and economics - De Gennaro, Davide; Marino, Marco (Emerald Publishing Limited, 2024)
In an increasingly globalized world, the face of higher education--particularly in the fields of business and economics--is evolving rapidly. Classrooms are more culturally diverse than ever, reflecting a kaleidoscope of backgrounds, perspectives, and learning styles. Offering educators strategies for navigating culturally diverse classrooms Global Classroom addresses the challenges, effective communication techniques, inclusive curricula, and real-world case studies in business and economics education. Acknowledging the need for more discussion in the literature as business becomes more global, and as students are not just learning to operate within their home countries; they are learning to engage with different cultures and economic systems, the chapters confront methodologies that are still grounded in Western-centric ideologies and raises awareness of the complexities involved in teaching a culturally diverse student body. Seeking to arm educators with specific strategies to tackle challenges, such as language barriers, ethnocentric curricula, and varying degrees of familiarity with technology in a constantly more globalized and multicultural environment, the chapters act as a catalyst for instigating institutional change by providing administrators and policymakers with insights into the need for more inclusive pedagogical training and resources. Weaving in real-world case studies and expert interviews and placing special emphasis on the case study of Sant'Anna Institute in Sorrento, Italy, this book combines theory with practical advice and serves as a timely and essential tool for educators, administrators, and policymakers engaged in business and economics education in a culturally diverse setting.
Keywords: Business education.; Multicultural education.; Business & Economics -- Education.; Educational: Business studies and economics.; Business studies: general.; elektronické knihy; electronic books